Utilization of agro-food industry by-products in the finishing of culled dairy cows: Effects on meat quality - Bunmee T. (Chiang Mai University, 2015)
This study evaluated the effect of finishing strategies with different agro-industrial byproducts on meat quality of culled dairy cows. Culled dairy cows (n = 32) were kept individually and allotted to one of four treatments. A control group (C) was slaughtered immediately after culling-off. All others were subjected to a finishing period of 12 weeks. A forage group was fed with ad lib corn silage (F). Additionally there were a high-energy group (6 kg/day of cassava pulp + ad lib corn silage; F+) and a low-energy group (6 kg/day of crude rice bran + ad lib corn silage; F-) both based on by-products. The longissimus dorsi muscle was excised 24 h post-mortem and stored at -20°C prior to analysis. There were no significant effects of finishing treatment on meat color of all groups. Drip, thawing and cooking losses were not statistically different between groups. The meat of C had significantly higher percentage of protein and tended to have more moisture than the other groups. Meat of the group F+ had the highest contents of fat and cholesterol. There was no significant effect by treatment on Warner-Bratzler shear force although shear force tended to be lowest with F+. The meat's contents of soluble and insoluble collagen were not significantly different among treatment groups.